Features and content of gender education of women-leaders in the activities of non-governmental organizations and movements (Pedagogy of Higher and Secondary Education, 2006)
The paragraph и dedicate io the actual problem of introducing Gender’s education in the Pedagogical and theoretical analysis of the specific nature Gender's upbringing women leader in the activity social organizations and movements.
Keywords: gender; gender education; woman-leader; social movement